Leaning towards resilience: mapping and exploring the literature on lean management - Anil Yasin Ar (Production and Manufacturing Research: An Open Access Journal)
Unprecedented disruptions from COVID-19 compelled firms to alter daily operations, leading many to adopt lean management practices as a coping strategy. However, the literature lacks clarity on which practices most effectively enhance resilience. Addressing this gap, this paper systematically maps the domain using the PRISMA protocol, analyzing 68 manuscripts from Scopus and Web of Science (2020–2023). Findings reveal that lean management significantly strengthens data processing, value mapping, and resource allocation, collectively improving enterprise resilience. Specifically, practices such as big data optimization, scenario analysis, and AI-based automation emerged as essential tools during COVID-19. This study offers theoretical and practical insights, elucidating how lean management enhances resilience, contributes to enterprise resilience, and advances the field of lean management research.